Maintenance of Viral Suppression in Human Immunodeficiency Virus Controllers Despite Waning T-Cell Responses During Antiretroviral Therapy. (4th June 2020) - Jilg, Nikolaus; Garcia-Broncano, Pilar; Peluso, Michael; Segal, Florencia P; Bosch, Ronald J; Roberts-Toler, Carla; Chen, Samantha M Y; Van Dam, Cornelius N; Keefer, Michael C; Kuritzkes, Daniel R; Landay, Alan L; Deeks, Steven; et al.
Abstract: AIDS Clinical Trials Group study A5308 found reduced T-cell activation and exhaustion in human immunodeficiency virus (HIV) controllers start antiretroviral therapy (ART). We further assessed HIV-specific T-cell responses and post-ART viral loads. Before ART, the 31% of participants with persistently undetectable viremia had more robust HIV-specific T-cell responses. During ART, significant decreases were observed in a broad range of T-cell responses. Eight controllers in A5308 and the Study of the Consequences of the Protease Inhibitor Era (SCOPE) cohort showed no viremia above the level of quantification in the first 12 weeks after ART discontinuation. ART significantly reduced HIV-specific T-cell responses in HIV controllers but did not adversely affect controller status after ART discontinuation. Abstract : In a large cohort of human immunodeficiency virus (HIV) controllers (AIDS Clinical Trials A5308), HIV-specific T-cell responses were higher in nonviremic than in viremic controllers. Despite decreasing T-cell responses on antiretroviral therapy, controller status was preserved after therapy was stopped.